2002
DOI: 10.1034/j.1600-051x.2002.290513.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease and periodontitis − a case control study in Chilean adults

Abstract: The results are in accordance with those of several previous reports. If the results reflect a causal link between periodontal diseases and CHD they emphasize the need for better control of periodontal diseases. If the associations are-non-causal, they still demonstrate that CHD and periodontal diseases cluster in the same sections of the population, which is important from a public health point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 23 publications
5
45
1
2
Order By: Relevance
“…Andriankaja et al [13] reported a slightly lesser effect of CAL on MI, obtaining OR 1.34 (95% CI = 1.15-1.57) for men and OR 2.08 (95% CI = 1.47-2.94) for women after adjustment for age, BMI, physical activity, diabetes and smoking. Likewise, López et al [11] received crude OR 3.78 (95% CI = 1.60-8.92) and adjusted OR 3.17 (1.31-7.63) after adjusting for diabetes, systolic blood pressure and smoking. This can partly be explained by the fact that the study by López et al [11] included a younger age group of 30-50 years, where lower CAL values can be expected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Andriankaja et al [13] reported a slightly lesser effect of CAL on MI, obtaining OR 1.34 (95% CI = 1.15-1.57) for men and OR 2.08 (95% CI = 1.47-2.94) for women after adjustment for age, BMI, physical activity, diabetes and smoking. Likewise, López et al [11] received crude OR 3.78 (95% CI = 1.60-8.92) and adjusted OR 3.17 (1.31-7.63) after adjusting for diabetes, systolic blood pressure and smoking. This can partly be explained by the fact that the study by López et al [11] included a younger age group of 30-50 years, where lower CAL values can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, López et al [11] received crude OR 3.78 (95% CI = 1.60-8.92) and adjusted OR 3.17 (1.31-7.63) after adjusting for diabetes, systolic blood pressure and smoking. This can partly be explained by the fact that the study by López et al [11] included a younger age group of 30-50 years, where lower CAL values can be expected. On the other hand, Cueto et al [12] observed a stronger association between periodontitis and MI with OR = 4.42 (95% CI = 2.22-8.82).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations